Assessment of Selected Physiological and Immunological Parameters in a Sample of Obese Patients in Samarra City - Khalida Khaleel Abdullah; Hadeer Hussein Alwan; Asmaa Ismael Hussein; Saif al deen Mamdoh Khatlan (Universitas Muhammadiyah Sidoarjo, 2025)
The present study was conducted to assess the hormone's levels (nesfatin-1, leptin, resistin and adiponectin) on some of inflammatory cytokines or the so-called adipokines which exert a variety of biological activities (tumor necrosis factor alpha: TNF-α and interleukin-6 IL6), as well as BMI & lipid profile in serum of obese women in Samarra 10. The present study had included (50) samples, and they were divided into: 25 samples of obese women age ranged between (25-45) years, and (25) samples for the control group that constituted from women with normal weight. The results of the study demonstrated a marked elevation in the levels of leptin and resistin hormonal levels, inflammatory cytokines, i.e., tumor necrosis factor-α (TNF-α) interleukin -6 (IL-6), lipid profile evaluated by body mass index ) as well as significant decline in nesfatin-1 and adiponectin at the significance level represented by mean± SD: (P≤0.05) among obese women compared with control group. Highlights: Obese women showed significantly higher serum levels of leptin, resistin, TNF-α, IL-6, and lipid profile abnormalities compared to controls. Nesfatin-1 and adiponectin levels were markedly reduced in obese patients, indicating impaired appetite regulation and anti-inflammatory response. Findings confirm obesity as a state of chronic low-grade inflammation, linking it to increased risk of diabetes and cardiovascular disease.